2005
DOI: 10.1002/pros.20243
|View full text |Cite
|
Sign up to set email alerts
|

Small G‐protein RhoE is underexpressed in prostate cancer and induces cell cycle arrest and apoptosis

Abstract: In conclusion, our findings suggest RhoE as a tumor suppressor gene that is downregulated early in the development of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 24 publications
7
67
0
Order By: Relevance
“…A recent report found complete loss of expression or reduced expression of RhoE in prostate cancer compared with the benign prostate. 16 Another research also showed that RhoE gene was amplified 9.44-fold in the epithelial cell of the parous breast compared with that of nulliparous breast. 19 Considering that RhoE may play a role in carcinogenesis through changes of expression, in this study, we examined RhoE expressions both quantitatively and qualitatively in a sample of 30 lung cancer tissues and the background lung tissues.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent report found complete loss of expression or reduced expression of RhoE in prostate cancer compared with the benign prostate. 16 Another research also showed that RhoE gene was amplified 9.44-fold in the epithelial cell of the parous breast compared with that of nulliparous breast. 19 Considering that RhoE may play a role in carcinogenesis through changes of expression, in this study, we examined RhoE expressions both quantitatively and qualitatively in a sample of 30 lung cancer tissues and the background lung tissues.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, restoration of RhoE expression in prostate cancer cells inhibits cancer cell growth and results in G 2 /M arrest, indicating RhoE may act as a tumor suppressor. 16 On the other hand, the levels of RhoE expression are significantly higher in the prostate cancer cell lines with high metastatic potential compared with those with low metastatic potential, 17 suggesting a role for RhoE in metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Using a combination of cell culture, ex vivo, and in vivo approaches, we have identified evidence supporting that Rnd3 has barrier‐protective properties under certain conditions, such as following acute inflammatory challenge. The involvement of Rnd3 in the control of endothelial barrier function adds to a growing list of recently described functions ascribed to Rnd family proteins, including Ca 2+ homeostasis in the heart,53 regulation of Notch1 signaling,54 control of cell cycle progression,55, 56, 57 development of the central nervous system,58, 59, 60 control of cell motility and metastatic potential of certain cancers,29, 61, 62, 63, 64 and a potential role in cardioprotection against heart failure 65. In addition, we provide novel evidence that delivery of Rnd3 protein can serve as a potential therapeutic tool to ameliorate microvascular hyperpermeability caused by tissue injury.…”
Section: Discussionmentioning
confidence: 99%
“…KRT18 is a cytokeratin known to be expressed in the umbrella layer of urothelium whose expression increases with urothelial carcinogenesis [25]. ARHE (also 'Rho family GTPase 3' (RND3)) is a Rho signal transduction member with roles in many cellular processes (cytoskeleton organization, membrane trafficking, cell growth and apoptosis) [29], whose loss is reported in prostate cancer. Deranged DNA repair is represented by BRCA2 and LIG3 [30].Whilst neither is directly linked with bladder carcinogenesis, it is possible that loss of both is required for carcinogenic alteration.…”
Section: Discussionmentioning
confidence: 99%